Solutions to improve digital marketing activities for domestic tour products of VITRACO Tourist Transport & Joint Stock Company Limited - Truong, Thi Thu Thao (Vietnam-Korea University of Information and Communication Technology, 2024)
Bachelor thesis of Business Administration - Digital Marketing